Inclusive Education: Enhancing Social Integration and Academic Achievement for Students With and Without Learning Disabilities Aged 5 to 14 - HUỲNH, TÂN; Nguyen, Nam Thi Thuy (VNU Journal of Science: Education Research, 2024)
Inclusive education is recognized as essential for fostering the holistic development of children, irrespective of their abilities or limitations. This paper examines the effects of inclusive education on students with learning disabilities (SWLD) and students without learning disabilities (SWOLD) in Southern Vietnam, focusing on its impact on social integration and academic achievement. The study employs a mixed-methods research design, combining qualitative interviews with educators and quantitative analysis of student performance data. There are 487 participants, consisting of 132 SWLD and 355 SWOLD. These participants were drawn from inclusive and non-inclusive schools across various educational levels in southern Vietnam. Results indicate that inclusive practices significantly enhance social integration, empathy, and understanding among students. For SWLD, inclusive education leads to improved academic outcomes, particularly in the early education stages, while SWOLD reports favourable or neutral effects on academic achievements. However, at the secondary education level, the impact tends to be neutral or adverse for SWOLD. The research also identifies challenges in Southern Vietnam, including insufficient funding, inadequate teacher training and limited policy support, which hinder the effective implementation of inclusive education. Addressing these barriers is crucial for creating an equitable learning environment for all students in Vietnam.